Studi Kelayakan Finansial Usaha Roti Hamimah Di Desa Rambah Kecamatan Rambah Hilir Kabupaten Rokan Hulu - mukmin, abdul (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
Bussiness feasibility study is needed to see a figure out of feasibility to run a business. Incarrying out the business of bread Hamimah agro-industry, most employers have notmade a special recording of finance for their business, so it is not known how much itsexpenses cost and revenue expenditure on its business. This research purpose to analyzethe financial feasibility of bread Hamimah agro-industry and knowing the problemsfaced.Method ofanalysis usesfeasible analysis from various aspect such as market andmarketing aspects, technical aspects, financial aspects,in addition sensitivities analysisalso used to asses input of cost increase toward business feasibility.This research wasconducted from November 2015 until February 2016. Data collection methods used weresurveys and direct interviews with respondents. The results of a financial analysis on tofuagro-indutry business as feasible with Net Present Value (NPV) of Rp.2,184,214,511,- ispositive (NPV> 0), Internal Rate of Return (IRR) IRR 15,86% which is greater discountfactor that applies, namely 12.95%, Net B / C is 1,3099 where the Net B / C> 1, Pay Backperiod (PBP) 1 months5 day, and Break Even Point (BEP) 5 years 9 months 20 days,meaning not experience gains and losses before the economic life of the equipmentexpires.The results of the sensitivity analysis declared eligible by the increase inoperating costs by 18% the selling price fixed and the selling price sensitivity analysis18% and fixed production costs feasible declared.All result were analyzed with theinvestment criteria states that enterprises in Mr.Sudarsoâs bread agro-industry isfeasible.